Pengaruh Kepemimpinan Otentik, Budaya Inovasi, dan Dukungan Rekan Kerja terhadap Kreativitas Pegawai - Juliadi, Juliadi; Herman, Hendri; Suyono, Suyono (eScience Humanity Journal, 2025)
This study aims to analyze the influence of authentic leadership, innovation culture, and coworker support on employee creativity at the Regional Revenue Agency of Batam City. Employee creativity is a strategic factor in improving public sector organizational performance, particularly in responding to increasing demands for service quality and regional revenue management. This research employed a quantitative approach using a survey method. The research population consisted of all employees of the Regional Revenue Agency of Batam City, with a saturated sampling technique applied so that the entire population was used as respondents. Data were collected through structured questionnaires developed based on indicators of each research variable. Data analysis was conducted using multiple linear regression to examine the partial and simultaneous effects among variables. The results indicate that authentic leadership has a positive and significant effect on employee creativity. Innovation culture also has a positive and significant influence in fostering creative ideas in the workplace. Furthermore, coworker support shows a positive and significant effect on employee creativity. Simultaneously, authentic leadership, innovation culture, and coworker support significantly affect employee creativity. These findings highlight the importance of authentic leadership, an innovative organizational culture, and a supportive work environment in enhancing employee creativity in the public sector